Analysis of surgical interruption of the enterohepatic circulation as a treatment for pediatric cholestasis. Issue 5 (22nd March 2017) - Wang, Kasper S.; Tiao, Greg; Bass, Lee M.; Hertel, Paula M.; Mogul, Douglas; Kerkar, Nanda; Clifton, Matthew; Azen, Colleen; Bull, Laura; Rosenthal, Philip; Stewart, Dylan; Superina, Riccardo; et al.
Abstract : To evaluate the efficacy of nontransplant surgery for pediatric cholestasis, 58 clinically diagnosed children, including 20 with Alagille syndrome (ALGS), 16 with familial intrahepatic cholestasis‐1 (FIC1), 18 with bile salt export pump (BSEP) disease, and 4 others with low γ‐glutamyl transpeptidase disease (levels <100 U/L), were identified across 14 Childhood Liver Disease Research Network (ChiLDReN) centers. Data were collected retrospectively from individuals who collectively had 39 partial external biliary diversions (PEBDs), 11 ileal exclusions (IEs), and seven gallbladder‐to‐colon (GBC) diversions. Serum total bilirubin decreased after PEBD in FIC1 (8.1 ± 4.0 vs. 2.9 ± 4.1 mg/dL, preoperatively vs. 12‐24 months postoperatively, respectively; P = 0.02), but not in ALGS or BSEP. Total serum cholesterol decreased after PEBD in ALGS patients (695 ± 465 vs. 457 ± 319 mg/dL, preoperatively vs. 12‐24 months postoperatively, respectively; P = 0.0001). Alanine aminotransferase levels increased in ALGS after PEBD (182 ± 70 vs. 260 ± 73 IU/L, preoperatively vs. 24 months; P = 0.03), but not in FIC1 or BSEP. ALGS, FIC1, and BSEP patients experienced less severely scored pruritus after PEBD (ALGS, 100% vs. 9% severe; FIC1, 64% vs. 10%; BSEP, 50% vs. 20%, preoperatively vs. >24 months postoperatively, respectively; P < 0.001). ALGS patients experienced a trend toward greater freedom from xanthomata after PEBD. There was a trend toward decreased pruritus in FIC1 after IE and GBC. Vitamin K supplementation increased in ALGS after PEBD (33% vs. 77%; P = 0.03). Overall, there were 15 major complications after surgery. Twelve patients (3 ALGS, 3 FIC1, and 6 BSEP) subsequently underwent liver transplantation. Conclusion : This was a multicenter analysis of nontransplant surgical approaches to intrahepatic cholestasis. Approaches vary, are well tolerated, and generally, although not uniformly, result in improvement of pruritus and cholestasis. (Hepatology 2017;65:1645‐1654).